Injectable Magnesium-Zinc Alloy Containing Hydrogel Complex for Bone Regeneration - Wang, Wei-Hua; Wang, Fei; Zhao, Hai-Feng; Yan, Ke; Huang, Cui-Ling; Yin, Yin; Huang, Qiang; Chen, Zao-Zao; Zhu, Wen-Yu (Frontiers in Bioengineering and Biotechnology, 2020)
Gelatin methacryloyl (GelMA) has been widely used in bone engineering. It can also be filled into the calvarial defects with irregular shape. However, lack of osteoinductive capacity limits its potential as a candidate repair material for calvarial defects. In this study, we developed an injectable magnesium–zinc alloy containing hydrogel complex (Mg-IHC), in which the alloy was fabricated in an atomization process and had small sphere, regular shape, and good fluidity. Mg-IHC can be injected and plastically shaped. After cross-linking, it contents the elastic modulus similar to GelMA, and has inner holes suitable for nutrient transportation. Furthermore, Mg-IHC showed promising biocompatibility according to our evaluations of its cell adhesion, growth status, and proliferating activity. The results of alkaline phosphatase (ALP) activity, ALP staining, alizarin red staining, and real-time polymerase chain reaction (PCR) further indicated that Mg-IHC could significantly promote the osteogenic differentiation of MC3T3-E1 cells and upregulate the genetic expression of collagen I (COL-I), osteocalcin (OCN), and runt-related transcription factor 2 (RUNX2). Finally, after applied to a mouse model of critical-sized calvarial defect, Mg-IHC remarkably enhanced bone formation at the defect site. All of these results suggest that Mg-IHC can promote bone regeneration and can be potentially considered as a candidate for calvarial defect repairing.